ЕЕГ аналіз розподілу уваги в лівшів та правшів при проходженні емоційного Струп-тесту на фоні пред’явлення зображень IAPS - Бондаренко (Рассомагіна), Марія; Бондаренко, Олександр; Кравченко, Вікторія; Макарчук, Микола; Bondarenko (Rassomagina), Maria; Bondarenko, Alexander; Kravchenko, Victoriya; Makarchuk, Mukola (Східноєвропейський національний університет імені Лесі Українки, 2015)
Оцінювали спектральну потужність та коефіцієнт когерентності основних ритмів ЕЕГ (тета-, альфа-, бета- низькочастотний, бета-високочастотний) під час емоційного Струп-тесту на фоні зображень IAPS у лівшів та правшів із відкритим домінантним і недомінантним оком. Evaluated spectral power and coherence factor of the main EEG rhythms (theta, alpha, beta low-frequency, beta high-frequency) during the emotional Stroop-test on the background of IAPS images in left-handers and right-handers during perception through dominant and nondominant eye. Information that comes to analyzing structures of the brain through the dominant visual channel analyzed faster than that comes through the nondominant visual channel that is typical only for left-handers. Significant changes were shown for LP reactions of the nondominant hand on the neutral words and the dominant hand on the emotional words for both right-handers and left-handers. According to the EEG-correlates learning effect is present during perception of information through the left eye for left-handers and right-handers.
EEG Analysis of the Distribution of Attention in Left-handers and Right-handers During Emotional Stroop-test on the Background of IAPS Images
Keywords: IAPS; емоційний Струп-тест; домінантне око; недомінантне око; emotional Stroop-test; dominant eye; nondominant eye